the MANAJEMEN PELAKSANAAN PROGRAM KURSUS BAHASA ARAB INTENSIF DI PONDOK PESANTREN DARUL LUGHAH WA AL-DIRASAT AL-ISLAMIYAH - Khoirul Bariyah Khairul Bariyah; Nurlaila Nurlaila (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Nurul Hakim, 2023)
This research discusses the management of the implementation of the Arabic language course program which is carried out intensively at the Darul Lughah Wa Al-Dirasat al-Islamiyah Islamic boarding school as well as problems in the management of the implementation of the Arabic language course program at the boarding school. This research uses descriptive qualitative research methods. Data collection was carried out using observation, interviews and documentation techniques. Data analysis in this research was carried out using interactive qualitative analysis consisting of data reduction, data presentation, and drawing conclusions. The results of this research show that the implementation management of the Arabic language course program at the DLWI Islamic boarding school has gone very well. We can see this in the capabilities of the Islamic boarding school graduates who are qualified and able to compete with graduates of other Arabic-based Islamic boarding schools. To maximize participants' language skills, Arabic is used as a daily communication tool. The problems faced at this Islamic boarding school in the Arabic language course program at the Darul Lughah Wa Al-Dirasat Al-Islamiyah Islamic boarding school are from the teaching staff, infrastructure and committee in the course program. However, even though there were three problems in the activities of the intensive course program, the program continued to run smoothly and within one month the course program participants were able to speak and master Arabic well and correctly.